Encyclopaedia of global warming - Syed, M. H.; Khan, M. M. (Encyclopaedia of global warming, 2008)
Global warming is a current and burning topic, today. To comprehend, it is: th E gradual increase in the overall temperature of the earth`s atmosphere, due to increased level of carbon dioxide and other pollutants.` Extreme weather events, rise in the sealevel and a plethora of diseases are some of the serious concerns, which have drawn attention of policy-makers and scientists. It has a number of negative effects on, say, natural systems and creatures, such as butterflies, alpine herbs, life cycle of birds and plantation, etc. Given its harmful impacts, initiatives have been taken, both on na.